Negative Self-Concept: Cross-Country Evidence of Its Importance for Understanding Motivation and Academic Achievement - Yu Gao; Farhan Ali (MDPI AG, 2024)
Academic self-concept, the belief in one's ability, is a key motivational construct in educational psychology and large-scale assessments. The construct is typically measured by instruments with positively ("I usually do well in science") and negatively worded items ("I am just not good in science"). A single latent factor is often assumed. Here, we investigated this assumption using international large-scale assessment data across two age groups of children in fourth grade and adolescents in eighth grade (N = 296,320 students, 23 educational systems). We, instead, found strong evidence of the substantiveness of a negative self-concept factor derived from negatively worded items. Exploratory and confirmatory factor analyses uncovered negative self-concept as being distinct from positive self-concept. Furthermore, theory-driven modeling supported the internal/external (I/E) frame of reference model effect on negative self-concept: achievement has a stronger effect on eighth graders' negative self-concept relative to fourth-grade children across many countries, especially for mathematics. Overall, understanding students' negative appraisals and negative beliefs of their ability is an important theoretical and policy imperative.